2018
DOI: 10.5194/acp-18-1003-2018
|View full text |Cite
|
Sign up to set email alerts
|

Regional simulation of Indian summer monsoon intraseasonal oscillations at gray-zone resolution

Abstract: Abstract. Simulations of the Indian summer monsoon by the cloud-permitting Weather Research and Forecasting (WRF) model at gray-zone resolution are described in this study, with a particular emphasis on the model ability to capture the monsoon intraseasonal oscillations (MISOs). Five boreal summers are simulated from 2007 to 2011 using the ERA-Interim reanalysis as the lateral boundary forcing data. Our experimental setup relies on a horizontal grid spacing of 9 km to explicitly simulate deep convection withou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…PolarWRF model options are detailed in supporting information S1 (Bigg, 1953;Bromwich et al, 2013;Chen et al, 2018;Dearden et al, 2016;Nakanishi & Niino, 2006;Prein et al, 2015). The model was run for 48 hr, to allow adequate time for spin up, at high spatial resolution.…”
Section: 1029/2018gl080551mentioning
confidence: 99%
“…PolarWRF model options are detailed in supporting information S1 (Bigg, 1953;Bromwich et al, 2013;Chen et al, 2018;Dearden et al, 2016;Nakanishi & Niino, 2006;Prein et al, 2015). The model was run for 48 hr, to allow adequate time for spin up, at high spatial resolution.…”
Section: 1029/2018gl080551mentioning
confidence: 99%
“…Their results show that the gray-zone resolution simulation was able to realistically replicate the general precipitation, circulation, thermodynamic, and radiation features of the October and November MJO events observed during DYNAMO. Subsequent work by Chen et al (2018b) showed that the gray-zone resolution simulation can capture the general features of atmospheric overturning across different scales well. Similar model setups have also been used to study the physical mechanisms of tropical convection (Zhang et al 2017;Chen et al 2018a,c;Chen and Zhang 2019).…”
Section: Experimental Design a Forecast Model Domain Of Interest And Ensemble Setupmentioning
confidence: 99%
“…The same physical schemes were used in the D01 and D02, including the WRF Double-Moment 6class microphysics scheme (Lim & Hong, 2010), the longwave radiation scheme of Rapid Radiative Transfer Model for general circulation model applications (Iacono et al, 2008), the New Goddard shortwave radiation scheme (Chou & Suarez, 1999), the Monin-Obukhov similarity surface-layer scheme (Paulson, 1970) (Hong et al, 2006). No cumulus parameterization scheme was used in either of the model domains (D01 and D02), which follows Chen et al (2018). Note that the data assimilation method used by the WRF-EnKF system presented here is ensemble based, which is drastically different from those variational methods used for creating ERA-Interim and ERA5, the IFS Cycle 31r2 4DVAR and IFS Cycle 41r2 4DVAR (Hersbach & Dee, 2016), respectively, besides their differences in model, resolution, and physics parameterization schemes.…”
Section: Forecast Modelmentioning
confidence: 99%